AFTER ELIOT: ADAPTING ADAM BEDE. (September 2014) - Reynolds, Margaret
Abstract: George Eliot's novel Adam Bede was first published in 1859. The story has since been adapted for stage and screen. This article considers two nineteenth-century stage adaptations (1862 and 1884 – from manuscripts in the British Library), two silent film versions (1915 and 1918), one stage dramatization (1990), a television film (1991), and a radio adaptation (2001) to consider how these appropriations relate to one another and how they vary in different historical settings. The key starting point for Eliot was the story of Mary Voce, a woman executed in 1802 for the murder of her child. This article argues that, as the story is transformed in these later remediations, it is the character and fate of Hetty Sorrel that undergoes most telling change in performance.